Inhibition of quorum sensing controlled virulence factors in escherichia coli 0157-H7 by dietary plant extracts - Suraya Hamid (2009)
Quorum sensing (QS) is a cell-to-cell communication mechanism in bacteria that regulates gene expression in response to cell population density, mediated by signal molecules known as autoinducers. Pathogenic bacteria such as Escherichia coli O157:H7 utilize quorum sensing to regulate virulence genes, contributing to infection processes. This study screened several ethanol-based plant extracts—namely garlic (Allium sativum), sand ginger (Kaempferia galanga), pandan leaves (Pandanus amaryllifolius), and kaffir lime leaves (Citrus hystrix)—for potential quorum sensing inhibition. Using the acyl-homoserine lactone (AHL) reporter strain Chromobacterium violaceum, all extracts demonstrated the ability to inhibit or modulate violacein production at sub-lethal concentrations, suggesting interference with quorum sensing-regulated phenotypes.